2021
DOI: 10.2147/dmso.s305511
|View full text |Cite
|
Sign up to set email alerts
|

T-Natural Killers and Interferon Gamma/Interleukin 4 in Augmentation of Infection in Foot Ulcer in Type 2 Diabetes

Abstract: Background The link between immune system and type 2 diabetes mellitus (T2DM) pathogenesis attracted attention to demonstrate the role of immune cells and their secreted cytokines in T2DM development and its subsequent foot complications. Objective To investigate the relation between T Natural killer cell (TNK) %, Interleukin 4 (IL4) and Interferon gamma (IFN-γ) and diabetic foot infection (DFI) development in patients with diabetic foot ulcer (DFU). Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“… 32 , 33 These findings seem to be consistent with the results of a previous study indicating that serum NKT% and IFN-γ were significantly decreased in patients with diabetic foot infection compared to patients with non-infected DFUs and diabetes only. 34 Furthermore, cigarette smoking can systemically decrease immune responses, leading to ESKAPE infection. 35 It has been shown that hyperglycemia affects the vasoconstriction response and platelet aggregation by inhibiting endothelial nitric oxide synthase activation and increasing reactive oxygen species, leading to atherothrombosis in the vessels and ultimately to peripheral vascular disease.…”
Section: Discussionmentioning
confidence: 99%
“… 32 , 33 These findings seem to be consistent with the results of a previous study indicating that serum NKT% and IFN-γ were significantly decreased in patients with diabetic foot infection compared to patients with non-infected DFUs and diabetes only. 34 Furthermore, cigarette smoking can systemically decrease immune responses, leading to ESKAPE infection. 35 It has been shown that hyperglycemia affects the vasoconstriction response and platelet aggregation by inhibiting endothelial nitric oxide synthase activation and increasing reactive oxygen species, leading to atherothrombosis in the vessels and ultimately to peripheral vascular disease.…”
Section: Discussionmentioning
confidence: 99%
“… 44 Compared to the type 2 diabetes mellitus group, a significant decrease in NKT and IFN-γ was observed in the diabetic foot infection group. 45 Based on the aforementioned findings, we posit that the TGF-β signaling pathway plays a significant role in the progression of DFU by modulating the infiltration of immune cells.…”
Section: Discussionmentioning
confidence: 95%
“… 26 A decrease in the frequency of NK cells plays a crucial role in the development of T2DM and its subsequent foot complications. 27 Chronic wounds, which are associated with dysregulated immune cells such as M1 macrophages, result from persistent inflammation and hinder the healing process of diabetic foot ulcers by disrupting the polarization of M2 macrophages. 28 The transition between classical and non-classical monocytes plays a crucial role in regulating inflammation and tissue repair during the healing of diabetic wounds.…”
Section: Discussionmentioning
confidence: 99%